MEDIASI PENAL SEBAGAI ALTERNATIF PENYELESAIAN PERKARA TINDAK PIDANA KECELAKAAN LALU LINTAS YANG MENGALAMI KERUGIAN MATERIAL OLEH KEPOLISIAN RESOR KOTA PEKANBARU - Lidya Astari; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Police investigators may actually conduct penal mediation through peace between the victim and the suspect in traffic accident cases suffering material loss. Polri has the authority to stop or continue a case in the criminal justice process for certain reasons. The legal basis that can be used is Article 18 paragraph (1) of Law Number 2 Year 2002 regarding the Police of the Republic of Indonesia, which reads for public and public interest, the officer of the Indonesian National Police in performing its functions, duties and authorities may act in its judgment own.The type of research used in the writing of this law is the study of sociological law by case study method is the method used to research the truth of an event / event that occurs by observing an object in the form of circumstances, individuals and communities. If viewed from the nature of this research is classified as descriptive. The study uses the primary data that is data obtained from the field through interviews and secondary data ie data that has been so.The result of this research is the implementation of penal mediation as an alternative to the settlement of traffic accidents case that experienced material loss by Pekanbaru Resort Police done when there is material loss and minor physical injury suffered by the victim, the mutual agreement between the two parties litigation ie victim and suspect or family related case traffic accidents suffered as well as compensation, a non-demanding statement from the victim to the case and did not want the case to proceed to the next stage; the investigator performs a title of the case against the traffic accident that has been resolved through the mediation of the penal. The obstacles in the implementation of mediation of penal as an alternative of case settlement in the case of traffic accident by Jember Police can be distinguished in 2 (two) internal factors, for example: in applying penal mediation to criminal cases because there is no clear and firm rules governing penal mediation but based solely on discretionary authority possessed by the police alone, there is no equal understanding of the investigators regarding the implementation of this penal mediation, as well as the absence of SOPs Standard Operating Procedure) concerning penal mediation mechanism on criminal case including in case of traffic accidents having material loss. External Factors, for example: victims who are not willing to be settled by penal mediation and still demand that the case be continued to the next stage, uncooperative suspects in the conduct of investigations thereby impeding penal mediation, the failure of the agreement between the victim and the suspect or his family.Keywords: penal mediation, criminal offense, traffic accident